The Moss Grimmia muhlenbeckii (Grimmiaceae) is Widespread in Eastern New York - N. G. Miller (Evansia, 2009)
Grimmia muehlenbeckii, hitherto unrecorded in the bryoflora of New York State, is documented from eight counties in a large part of eastern New York. In this region G. muehlenbeckii grows at low to middle altitude on calcareous, weakly calcareous, and acidic rock, usually on bedrock outcrops that are weathered. The earliest collection from this area dates to 1955.
Keywords: Grimmia muehlenbeckii; moss; New York